Immigration: The European Experience - Christian Dustmann; Tommaso Frattini (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2011)
This paper starts with a brief historical overview of immigration in Europe. We then provide a comprehensive analysis of the skill structures of immigrants and their labor market integration in the different European countries, their position in the wage distribution, and the situation of their children, and illustrate the economic situation of immigrants and their children relative to natives. We show that immigrants – in particular those from non-EU countries – are severely disadvantaged in most countries, even if we compare them to natives with the same measurable skills. We conclude with a discussion of the role of regulations and institutions as one possible mechanism for these findings, and suggest directions for future research.
Keywords: J15; J61; J62; 330; Immigration; Europe; Integration; Institutions